Answer:
radius = 1
Step-by-step explanation:
The equation of a circle in standard form is
(x - h)² + (y - k)² = r²
where (h, k) are the coordinates of the centre and r is the radius
(x - 2)² + (y + 3)² = 1 ← is in standard form
with r² = 1 ( take the square root of both sides )
r =
= 1
Answer:
√85
Step-by-step explanation:
A (-3 , 4) B (4 , -2)
AB² = (4 - -3)² + (-2 -4)² = 49 + 36 = 85
AB = √85
Answer:
12
Step-by-step explanation:
212113
The coefficient of y is 14 and the constant is 13.
You can find this by combining like terms first.
6x + 12y + 5 + 2y + 8
6x + 14y + 5 + 8
6x + 14y + 13
Now the coefficient is the number next to y. The constant is the number on its own.